Identifikasi Minyak Atsiri dalam Kalus Daun Lavender (Lavandula officinalis Chaix) dengan Perlakuan Penambahan Zat Pengatur Tumbuh NAA pada Medium MS - Ratno Agung Samsumaharto; Fransiska Leviana; Prapita Sari Widayanti (Jurnal Farmasi Indonesia, 2010)
Lavender (Lavandula officinalis Chaix) plant contains secondary metabolite such as volatile oil. Lavender oil can be used as antiseptic, anti-inflammation, repellant and antifeedant. The experiment was aimed to know the influence of NAA hormone in inducing lavender leaves callus and stimulating volatile oil in lavender leaf callus. The experiment was done by plant tissue culture technique. Explant cultivation in MS media with various NAA plant growth regulator concentrations, i.e. 1 mg/L, 2 mg/L, 3 mg/L. Observation and evaluation were conducted for the success of callus forming, callus induction time, and callus weight and then the volatile oil was analyzed by color test and TLC using mobile phase hexane-ethyl acetate (96:4) and stationary phase silica gel 60F254 and the spot was observed by anisealdehyde- H2SO4 spray. The result of the experiment showed that NAA plant growth regulator with difference concentrations affected callus formation 86,67%, the fastest callus induction time 5,69 days, and the biggest average weight of dry callus 0,070 gram. The callus obtained from tissue culture with addition of NAA plant growth regulator contained volatile oil component the same as mother plant.